The role of vascular elastography and carotid artery intima media thickness methods in the determination of non-syndromic ascending thoracic aortic aneurysm (Annals of Medical Research, 2021)
None
Keywords: Aneurysm; Atherosclerosis; Intima-Media Thickness; Vascular Elastography.